ETNO-NATIONAL TRADITIONS OF UZBEK FAMILIES - THE PECULIARITIES OF CUSTOMS AND DIFFERENCES WITH THE TRADITIONS OF OTHER COUNTRIES - Nosirova Dilfuza Nabievna (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, Uzbek families, the Kalash people on the slopes of the Himalayas in Pakistan, it describes the marriage ceremonies and customs of Japanese families, the inhabitants of the Indonesian island of Bali, and the Bondo tribe, northwest of the Machkand River, on the border of the Indian states of Orissa and Andhra.